Studies on external transportation development and spatial structure transformation of modern Kunming from a Southeast Asian perspective, 1885- 1945 - Zhang, Tianje; Zhang, Yuqi (International Planning History Society Proceedings, 2018)
From a regional perspective of Southeast Asia, the paper focuses on Kunming, a gateway between China and Southeast Asian countries. The research elucidates the planning ideas and construction process of external routes, via both land and air, such as Yunnan-Vietnam Railway, Yunnan-Burma Railway, Burma Road, Stilwell Road and Hump Airline in early 20th century. These external routes became the arteries of cargo transportation, and Kunming became a regional economic center and military command center during wartime. The paper further reveals the transformation of Kunming’s spatial structures influenced by these external routes, which accelerated Kunming’s urban growth along the traffic lines. The city center shifted to the Station area, where industrial and commercial developments also congregated. New industrial zones were planned to the east and north of the old city, where new passages brought more convenient transportations. The internal road network plan also emphasized the connection with new railway station and bus stations. The research construes the planning ideas and implementation, traces their theoretical origins, and uncovers their indigenous considerations.